What are the Factors Influencing the Information Technology Adoption in Asian Region? A Study of the B2C E-Commerce Systems Success - P John, Surej (Humanities, Arts and Social Sciences Studies, 2013)
During this decade, large numbers of researchers investigate the success factors of B2C e-commerce systems. This may be due to the increased popularity of internet and its wide range of applications on personal as well as business use. However, it is to be noted that majority of these studies were conceptual studies. Though some empirically validated studies were published on B2C e-commerce systems, very few focused on Asian consumers. The study aims to fill this gap by studying e-commerce success factors among Asian online consumers. Another important objective of this study is to re-specify the updated DeLone and McLean model by including essential factors such as trust and perceived cost of transactions, perceived value and thereby form a new model for measuring e-Commerce success.The research generated 7 inter related dimensions of e-commerce system success which are information quality, system quality, service quality, perceived cost, perceived value, online customer satisfaction and Repurchase Intention. Results show that the customer satisfaction and perceived value of the transactions are the two important factors primarily influencing Asian online users. Results show that online customer satisfaction is influenced by factors such as perceived value, service quality, information quality and system quality. This study also found the significant negative relationship between perceived cost and perceived value of the transactions while shopping online.